2020
DOI: 10.1016/j.mayocp.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevention, Diagnosis, and Management of Chronic Wounds in Older Adults

Abstract: Chronic wounds are common, disproportionately affect older adults, and are likely to be encountered by providers across all specialties and care settings. All providers should be familiar with basic wound prevention, identification, classification, and treatment approach, all of which are outlined in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 58 publications
(58 reference statements)
0
15
0
8
Order By: Relevance
“…Unhealed chronic wounds are characterized by a prolonged inflammatory phase, delayed cellular proliferation, poor re-epithelialization, and impaired angiogenesis [ 3 , 23 ]. Since wound healing is impaired in diabetic patients, previous studies have reported various modalities, however, controversial results concerning wound healing in diabetic patients were be found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unhealed chronic wounds are characterized by a prolonged inflammatory phase, delayed cellular proliferation, poor re-epithelialization, and impaired angiogenesis [ 3 , 23 ]. Since wound healing is impaired in diabetic patients, previous studies have reported various modalities, however, controversial results concerning wound healing in diabetic patients were be found.…”
Section: Discussionmentioning
confidence: 99%
“…Skin wound healing is a complex multistep process involving the coordination of activities of multiple tissue and cell types [ 1 ]. Diabetic foot ulcers are a significant intricacy of diabetes mellitus and are probably the major component of the diabetic foot [ 2 , 3 ]. Re-epithelialization, a vital cycle in the beginning phase of wound healing, is the consequence of the movement and multiplication of keratinocytes in the epidermal layer of the skin around the injury.…”
Section: Introductionmentioning
confidence: 99%
“…The self-healing property of an organism results in wounds healing within three months, depending upon the injury's severity. However, an uncontrolled infection transforms an acute infection into a chronic one that lasts for months or even years [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, for example, millions of patients are suffering from bone or skin imperfections. The treatment sums for these defects are USD 39 billion and USD 75 billion annually, respectively [2]. In addition, prolonged medicinal resources have caused a burden on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Perante a sua fisiopatologia, origina-se a presença do edema, que é o sinal "padrão ouro" das lesões venosas (Hoversten et al, 2020). A partir desse conhecimento e haja vista a complexidade dos mecanismos, a prevenção e tratamento se concretizam principalmente por meio do controle e manejo correto do edema existente.…”
Section: Introductionunclassified